High-transparency, high-strength and high-toughness epoxy resin composite material and preparation method thereof

By using modified nanofillers and cellulose nanocrystals to modify graphene oxide and other raw materials, combined with epoxy resin prepolymers, the problem that epoxy resin composites are difficult to have high transparency, high strength and high toughness at the same time is achieved, and high Properties of epoxy resin composite materials.

CN119144118APending Publication Date: 2024-12-17SOLOMON (CHANGZHOU) ALLOY NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333687.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing epoxy resin composite materials are difficult to maintain high transparency, high strength and high toughness at the same time, and lack research and development methods that combine these three properties.

Method used

Bisphenol A type epoxy resin prepolymer, bismaleimide modified phenolic epoxy resin prepolymer, epoxy silane prepolymer, etc. are used as raw materials, and modified nanofillers and cellulose nanocrystals are combined. Modified graphene oxide, and through specific formulations and preparation methods, a high transparency, high strength, and high toughness epoxy resin composite material is formed.

Benefits of technology

The high transparency, high strength and high toughness of epoxy resin composite materials are achieved, the dispersion uniformity of the material and the interaction of chemical bonds are enhanced, the processing conditions window is broadened, and the production stability and performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057695690000021
    Figure BDA0005057695690000021
  • Figure BDA0005057695690000111
    Figure BDA0005057695690000111
  • Figure BDA0005057695690000121
    Figure BDA0005057695690000121
Patent Text Reader

Abstract

The invention relates to a high-transparency, high-strength and high-toughness epoxy resin composite material and a preparation method, and belongs to the technical field of epoxy resin composite materials, the epoxy resin composite material comprises the following raw materials: an epoxy prepolymer, a curing agent, a nanofiller A, a nanofiller B and a synergistic additive. Different raw materials are selected and compounded as the curing agent, and the epoxy resin composite material formed by reaction of the curing agent and the epoxy prepolymer under the formula has high transparency. Besides, the nano-filler A and the nano-filler B are self-made, and meanwhile, the nano-filler A, the nano-filler B and the synergistic additive are compounded, so that the finished epoxy resin composite material has the characteristics of high transparency, high strength and high toughness through the synergistic effect of the nano-filler A, the nano-filler B and the synergistic additive; the technical problem that the epoxy resin composite material in the field cannot keep high transparency, high strength and high toughness at the same time is successfully solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of epoxy resin composite materials, and in particular, relates to a high-transparency, high-strength, high-toughness epoxy resin composite material and a preparation method thereof. Background Art

[0002] Thermosetting plastics are widely used in adhesives, coatings, bonding agents, electronic product packaging, printed circuit boards, aviation, aerospace, military industry and many other fields. Epoxy resin is a polymer compound containing two or more epoxy groups in the molecule. After reacting with a curing agent, it can generate a three-dimensional network structure with thermosetting properties. For a long time, the pursuit of high-performance epoxy resins has been the focus and difficulty of research for technicians in this field. The high performance of epoxy resins mentioned here is reflected in transparency, strength, toughness and other aspects. At present, although a large number of patents and papers have proposed methods to improve the single performance of epoxy resins, however, there has never been any report on methods that can simultaneously improve its transparency, strength and toughness. This is still a difficult problem that needs to be solved urgently.

[0003] Therefore, it is not difficult to see that the current market is extremely lacking in the research and development of epoxy resin composite materials with high transparency, high strength and high toughness and their preparation methods. Therefore, providing such composite finished products and their preparation methods has important practical significance and application value. Summary of the invention

[0004] The purpose of the present invention is to provide a high-transparency, high-strength and high-toughness epoxy resin composite material and a preparation method thereof, which solves the technical problem that the epoxy resin composite material existing in the prior art cannot maintain high transparency, high strength and high toughness at the same time.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0007]

[0008] As a preferred technical solution of the present invention, the epoxy prepolymer includes at least one of bisphenol A epoxy resin prepolymer, bismaleimide modified phenolic epoxy resin prepolymer, epoxy silane prepolymer and epoxy silicone prepolymer.

[0009] Furthermore, the bisphenol A type epoxy resin prepolymer: Sinochem Xingchen, Phoenix brand, grade E51, viscosity 10000mPa·s; the bismaleimide modified phenolic epoxy resin prepolymer: purchased from Guangzhou Haihong Chemical Co., Ltd., grade F48; the epoxy silane prepolymer: purchased from Zongyang County Sanjin Pigment Co., Ltd., grade SJ-6040A; the epoxy silicone prepolymer: purchased from Guangdong Evergrande New Materials Technology Co., Ltd., grade Kraft K-5312.

[0010] As a preferred technical solution of the present invention, the curing agent includes at least one of o-phenylenediol, ethylenediamine, methylhexahydrophthalic anhydride, boron trifluoride methanol complex, 1,1-thiocarbonyldiimidazole, triethylamine, bicyclic amidine, isophoronediamine, metaphenylenediamine, sebacic acid dihydrazide and stannous chloride.

[0011] Furthermore, the boron trifluoride methanol complex was purchased from Guangzhou Yuanfeng Chemical Technology Co., Ltd., CAS No. 2802-68-8, analytical grade; the 1,1-thiocarbonyldiimidazole was purchased from Guangdong Qianjin Chemical Reagent Co., Ltd., CAS No. 6160-65-2, analytical grade.

[0012] As a preferred technical solution of the present invention, the nano filler A includes any one of modified nano zirconium dioxide, modified nano alumina and modified nano silicon dioxide.

[0013] Furthermore, the modified raw material of the modified nano zirconium dioxide is nano zirconium dioxide, the modified raw material of the modified nano alumina is nano alumina, and the modified raw material of the modified nano silicon dioxide is nano silicon dioxide.

[0014] Furthermore, the preparation method of the nanofiller A is:

[0015] Deionized water and anhydrous ethanol are mixed evenly, and the pH is adjusted to obtain a mixed solution A. A modifier is added to the mixed solution A, mixed evenly, and stirred at a controlled temperature once. After stirring, a modified raw material is added, mixed evenly, and stirred at a controlled temperature a second time to obtain a slurry. The slurry is dried under controlled temperature, extracted with anhydrous ethanol, and an extracted powder is obtained. The extracted powder is dried under controlled temperature to obtain a nanofiller A.

[0016] Furthermore, the volume ratio of the deionized water to the anhydrous ethanol is 15:85; and the pH is adjusted by using a hydrochloric acid solution with a mass concentration of 10% to adjust the pH to 4-5.

[0017] Furthermore, the dosage ratio of the mixed solution A, the modifier and the modified raw material is 200-210 mL: 1-1.2 g: 9-10 g.

[0018] Furthermore, the modifier includes any one of n-propanol, n-pentanol, n-octanol and n-dodecyl alcohol.

[0019] Furthermore, the temperature of the first temperature-controlled stirring is 65-70°C, and the time is 4-6h; the temperature of the second temperature-controlled stirring is 65-70°C, and the time is 5-6h; the temperature of the temperature-controlled drying of the slurry is 80-85°C, and the time is 22-24h; the temperature of the temperature-controlled drying of the extracted powder is 80-85°C, and the time is 12-14h.

[0020] Furthermore, the average particle size of the nanofiller A is 2-40 nm, and the particle size distribution index is 1-1.10.

[0021] As a preferred technical solution of the present invention, the nanofiller B includes modified cellulose nanocrystals modified with graphene oxide.

[0022] Furthermore, the preparation method of the modified cellulose nanocrystal modified graphene oxide specifically comprises the following steps: dissolving graphene oxide and modified cellulose nanocrystals in N,N-dimethylformamide, ultrasonically dispersing and stirring, filtering, and vacuum drying to obtain modified cellulose nanocrystal modified graphene oxide.

[0023] Furthermore, the mass ratio of the graphene oxide to the modified cellulose nanocrystals is 2:1; and the amount of N,N-dimethylformamide added is just enough to dissolve the graphene oxide and the modified cellulose nanocrystals.

[0024] Furthermore, the temperature of the ultrasonic dispersion and stirring is 55-60°C, and the time is 30-40 minutes; the temperature of the vacuum drying is 75-80°C, and the time is 24-26 hours.

[0025] Furthermore, the modification method of the modified cellulose nanocrystals is:

[0026] The cellulose nanocrystals and DMSO-toluene solution are magnetically stirred evenly, and after the stirring is completed, a modifier is added and mixed evenly while stirring at a controlled temperature, cooled, washed and centrifuged to obtain modified cellulose nanocrystals.

[0027] Furthermore, the usage ratio of the cellulose nanocrystals, the DMSO-toluene solution and the modifier is 1-1.2 g: 300-320 mL: 1-1.2 g.

[0028] Furthermore, the cellulose nanocrystals were purchased from Guilin Sailun Technology Co., Ltd., with an average length of 30-50 nm, an average width of 2-10 nm, and a model of CNC-C.

[0029] Furthermore, the volume ratio of DMSO to toluene in the DMSO-toluene solution is 8:2.

[0030] Further, the modifier includes any one of 1-N-Boc-3-hydroxyazetidine, 1-benzyl-3-azetidine and 3-hydroxy-3-(2-hydroxyethyl)azetidine-1-carboxylic acid tert-butyl ester.

[0031] Furthermore, the temperature of the temperature-controlled stirring is 85-90° C., and the time is 22-24 hours; the cooling is cooling to room temperature; and the washing and centrifugation are washing with acetonitrile, ethanol and deionized water in sequence for 2-3 times and centrifuging.

[0032] Furthermore, the average stacking number of the modified cellulose nanocrystal-modified graphene oxide is ≤3 layers and the specific surface area is ≥28m 2 / g, bulk density <20g / L.

[0033] As a preferred technical solution of the present invention, the synergist includes at least one of ethylene dioleamide, ethylene bisstearic acid amide, alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, benzyl glycidyl ether, neopentyl glycol diglycidyl ether and phenyl glycidyl ether.

[0034] A method for preparing a high-transparency, high-strength and high-toughness epoxy resin composite material, specifically comprising the following steps:

[0035] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring with ultrasonic assistance under temperature control to obtain a mixture A;

[0036] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture with the aid of ultrasound under temperature control, sealing the mixture and allowing it to stand, to obtain a mixture B;

[0037] (3) The mixture B is placed under temperature control and allowed to stand, thereby obtaining a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0038] Furthermore, the temperature of the temperature-controlled ultrasonic stirring in step (1) is 40-70° C., and the time is 3-12 h.

[0039] Furthermore, in step (2), the temperature of the temperature-controlled ultrasonic-assisted stirring is 25-60° C., and the time is 1-6 hours; and the sealed standing time is 24-72 hours.

[0040] Furthermore, the temperature of the temperature-controlled standing in step (3) is 120-155° C., and the time is 3-9 hours.

[0041] Beneficial effects of the present invention:

[0042] (1) The present invention selects different raw materials to be compounded as a curing agent, and the epoxy resin composite material formed by the reaction of the curing agent under the formula of the present invention and the epoxy prepolymer has high transparency;

[0043] In addition, the invention prepares nanofillers A and nanofillers B by themselves, the surface of the nanofiller A is modified by a fatty alcohol modification method and has good dispersibility in the matrix, the nanofiller B has a small particle size, a narrow particle size distribution and good compatibility with the epoxy matrix, so the nanofillers A and the nanofillers B can be evenly dispersed in the matrix without affecting the transparency of the composite material; on this basis, a synergist is added, which, on the one hand, further improves the uniformity of dispersion of the nanofillers A and the nanofillers B in the matrix, improves the stability of the entire formula system in the actual processing and production process, and broadens the width of the processing condition window, and on the other hand, plays a certain brightening and transparency-enhancing effect on the epoxy resin; and after a large number of verifications, the nanofiller A, the nanofiller B and the synergist selected by the invention can play a synergistic effect, so that the finished epoxy resin composite material has high transparency.

[0044] (2) The fatty alcohol functional groups on the surface of the homemade nanofiller A of the present invention have excellent interaction with the epoxy resin matrix, which promotes the enhanced interaction force between the nanofiller A and the matrix and uniform dispersion. At the same time, since the modified raw material of the nanofiller A itself has high strength, it contributes high strength and high toughness in the system; and the hydroxyl functional groups and azo functional groups on the surface of the homemade nanofiller B can directly participate in the curing reaction of the epoxy resin and form a close chemical bond interaction with the epoxy resin matrix. In addition, the modified raw material of the nanofiller B, graphene oxide, itself has the characteristics of high strength, and thus contributes high strength and high toughness in the system. Therefore, the epoxy resin composite material product prepared under the formula of the nanofiller A, nanofiller B and synergistic additive raw materials selected in the present invention has the characteristics of high strength and high toughness. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] The bisphenol A epoxy resin prepolymer used in the embodiment of the present invention: Sinochem Xingchen, Phoenix brand, brand E51, viscosity 10000mPa·s; the bismaleimide-modified phenolic epoxy resin prepolymer used: purchased from Guangzhou Haihong Chemical Co., Ltd., brand F48; the epoxy silane prepolymer used: purchased from Congyang Sanjin Pigment Co., Ltd., brand SJ-6040A; the epoxy silicone prepolymer used: purchased from Guangdong Evergrande New Materials Technology Co., Ltd., brand Kraft K-5312; the boron trifluoride methanol complex used: purchased from Guangzhou Yuanfeng Chemical Technology Co., Ltd., CAS No. 2802-68-8, analytical grade; the 1,1-thiocarbonyldiimidazole used: purchased from Guangdong Qianjin Chemical Reagent Co., Ltd., CAS No. 6160-65-2, analytical grade; the above will not be repeated later.

[0047] Example 1

[0048] Prepare nano filler A, wherein the nano filler A includes modified nano zirconium dioxide, the modified raw material of the modified nano zirconium dioxide is nano zirconium dioxide, and the preparation method of the modified nano zirconium dioxide is:

[0049] Deionized water and anhydrous ethanol are mixed evenly at a volume ratio of 15:85, and a hydrochloric acid solution with a mass concentration of 10% is used to adjust the pH to 5 to obtain a mixed solution A, a modifier is added to the mixed solution A, mixed evenly, and stirred at 70°C for 4 hours, and after stirring, a modified raw material is added, mixed evenly, and stirred at 70°C to obtain a slurry, and the slurry is dried at 83°C for 24 hours, extracted with anhydrous ethanol to obtain an extracted powder, and the extracted powder is dried at 80°C for 12 hours to obtain modified nano zirconium dioxide, i.e., nano filler A;

[0050] The dosage ratio of the mixed solution A, the modifier and the modified raw material is 200mL:1g:9g;

[0051] The modifier includes n-dodecyl alcohol;

[0052] Prepare nano filler A, wherein the nano filler A comprises modified nano alumina, and the preparation method of the modified nano alumina is the same as the preparation method of the modified nano zirconium dioxide, except that the modified raw material of the modified nano alumina is nano alumina;

[0053] A nanofiller A is prepared, wherein the nanofiller A comprises modified nanosilicon dioxide. The preparation method of the modified nanosilicon dioxide is the same as the preparation method of the modified nanozirconium dioxide, except that the modified raw material of the modified nanosilicon dioxide is nanosilicon dioxide.

[0054] After testing, the average particle size of the modified nano zirconium dioxide prepared in this embodiment is 2nm, and the particle size distribution index is 1.10; the average particle size of the modified nano alumina is 21nm, and the particle size distribution index is 1.10; the average particle size of the modified nano silicon dioxide is 21nm, and the particle size distribution index is 1.10.

[0055] Prepare a nanofiller B, wherein the nanofiller B includes modified cellulose nanocrystals modified with graphene oxide, and the preparation method of the modified cellulose nanocrystals modified with graphene oxide specifically includes the following steps: dissolving graphene oxide and modified cellulose nanocrystals in N,N-dimethylformamide at a mass ratio of 2:1, ultrasonically dispersing and stirring at a temperature of 58° C. for 30 minutes, filtering, and vacuum drying at a temperature of 75° C. for 24 hours to obtain modified cellulose nanocrystals modified with graphene oxide, i.e., nanofiller B;

[0056] The amount of N,N-dimethylformamide added is just enough to dissolve the graphene oxide and the modified cellulose nanocrystals;

[0057] The modification method of the modified cellulose nanocrystal is:

[0058] The cellulose nanocrystals and DMSO-toluene solution were magnetically stirred evenly, and after the stirring was completed, the modifier was added and mixed evenly and the temperature was controlled at 88°C and stirred for 24 hours, and then cooled to room temperature, and washed with acetonitrile, ethanol and deionized water twice in sequence and centrifuged to obtain modified cellulose nanocrystals;

[0059] The cellulose nanocrystals used in this example were purchased from Guilin Sailun Technology Co., Ltd., with an average length of 50 nm and an average width of 6 nm, model CNC-C;

[0060] The usage ratio of the cellulose nanocrystals, the DMSO-toluene solution and the modifier is 1.2 g:300 mL:1 g;

[0061] The volume ratio of DMSO to toluene in the DMSO-toluene solution is 8:2;

[0062] The modifying agent includes 1-benzyl-3-azetidine.

[0063] After testing, the modified cellulose nanocrystals modified with graphene oxide prepared in this embodiment have an average stacking number of 3 layers and a specific surface area of ​​28m 2 / g, bulk density is 18g / L.

[0064] Example 2

[0065] Prepare nano filler A, wherein the nano filler A includes modified nano zirconium dioxide, the modified raw material of the modified nano zirconium dioxide is nano zirconium dioxide, and the preparation method of the modified nano zirconium dioxide is:

[0066] Deionized water and anhydrous ethanol are mixed uniformly at a volume ratio of 15:85, and a hydrochloric acid solution with a mass concentration of 10% is used to adjust the pH to 4.5 to obtain a mixed solution A, a modifier is added to the mixed solution A, mixed uniformly, and stirred at 65°C for 5 hours, and after stirring, a modified raw material is added, mixed uniformly, and stirred at 68°C to obtain a slurry, and the slurry is dried at 80°C for 23 hours, extracted with anhydrous ethanol, and an extracted powder is obtained, and the extracted powder is dried at 85°C for 13 hours to obtain modified nano zirconium dioxide, i.e., nano filler A;

[0067] The dosage ratio of the mixed solution A, the modifier and the modified raw material is 210mL:1.2g:9.5g;

[0068] The modifier includes n-pentanol;

[0069] Prepare nano filler A, wherein the nano filler A comprises modified nano alumina, and the preparation method of the modified nano alumina is the same as the preparation method of the modified nano zirconium dioxide, except that the modified raw material of the modified nano alumina is nano alumina;

[0070] A nanofiller A is prepared, wherein the nanofiller A comprises modified nanosilicon dioxide. The preparation method of the modified nanosilicon dioxide is the same as the preparation method of the modified nanozirconium dioxide, except that the modified raw material of the modified nanosilicon dioxide is nanosilicon dioxide.

[0071] After testing, the average particle size of the modified nano zirconium dioxide prepared in this embodiment is 40nm, and the particle size distribution index is 1; the average particle size of the modified nano alumina is 40nm, and the particle size distribution index is 1; the average particle size of the modified nano silicon dioxide is 2nm, and the particle size distribution index is 1.10.

[0072] Prepare a nanofiller B, wherein the nanofiller B includes modified cellulose nanocrystals modified with graphene oxide, and the preparation method of the modified cellulose nanocrystals modified with graphene oxide specifically includes the following steps: dissolving graphene oxide and modified cellulose nanocrystals in N,N-dimethylformamide at a mass ratio of 2:1, ultrasonically dispersing and stirring at a temperature of 55° C. for 40 minutes, filtering, and vacuum drying at a temperature of 78° C. for 25 hours to obtain modified cellulose nanocrystals modified with graphene oxide, i.e., nanofiller B;

[0073] The amount of N,N-dimethylformamide added is just enough to dissolve the graphene oxide and the modified cellulose nanocrystals;

[0074] The modification method of the modified cellulose nanocrystal is:

[0075] The cellulose nanocrystals and DMSO-toluene solution were magnetically stirred evenly, and after the stirring was completed, the modifier was added and mixed evenly and the temperature was controlled at 85°C and stirred for 22 hours, and then cooled to room temperature, and washed with acetonitrile, ethanol and deionized water three times in sequence and centrifuged to obtain modified cellulose nanocrystals;

[0076] The cellulose nanocrystals used in this example were purchased from Guilin Sailun Technology Co., Ltd., with an average length of 30 nm and an average width of 2 nm, model CNC-C;

[0077] The usage ratio of the cellulose nanocrystals, DMSO-toluene solution and the modifier is 1 g:310 mL:1.1 g;

[0078] The volume ratio of DMSO to toluene in the DMSO-toluene solution is 8:2;

[0079] The modifying agent includes 1-N-Boc-3-hydroxyazetidine.

[0080] After testing, the modified cellulose nanocrystal modified with graphene oxide prepared in this embodiment has an average stacking number of 3 layers and a specific surface area of ​​30m 2 / g, bulk density is 20g / L.

[0081] Example 3

[0082] Prepare nano filler A, wherein the nano filler A includes modified nano zirconium dioxide, the modified raw material of the modified nano zirconium dioxide is nano zirconium dioxide, and the preparation method of the modified nano zirconium dioxide is:

[0083] Deionized water and anhydrous ethanol are mixed uniformly at a volume ratio of 15:85, and a hydrochloric acid solution with a mass concentration of 10% is used to adjust the pH to 4 to obtain a mixed solution A, a modifier is added to the mixed solution A, mixed uniformly, and stirred at 68°C for 6 hours, and after stirring, a modified raw material is added, mixed uniformly, and stirred at 65°C to obtain a slurry, and the slurry is dried at 85°C for 22 hours, extracted with anhydrous ethanol to obtain an extracted powder, and the extracted powder is dried at 83°C for 14 hours to obtain modified nano zirconium dioxide, i.e., nano filler A;

[0084] The dosage ratio of the mixed solution A, the modifier and the modified raw material is 205mL:1.1g:10g;

[0085] The modifier includes n-propanol;

[0086] Prepare nano filler A, wherein the nano filler A comprises modified nano alumina, and the preparation method of the modified nano alumina is the same as the preparation method of the modified nano zirconium dioxide, except that the modified raw material of the modified nano alumina is nano alumina;

[0087] A nanofiller A is prepared, wherein the nanofiller A comprises modified nanosilicon dioxide. The preparation method of the modified nanosilicon dioxide is the same as the preparation method of the modified nanozirconium dioxide, except that the modified raw material of the modified nanosilicon dioxide is nanosilicon dioxide.

[0088] After testing, the average particle size of the modified nano zirconium dioxide prepared in this embodiment is 21nm, and the particle size distribution index is 1.05; the average particle size of the modified nano alumina is 2nm, and the particle size distribution index is 1; the average particle size of the modified nano silicon dioxide is 40nm, and the particle size distribution index is 1.

[0089] Prepare a nanofiller B, wherein the nanofiller B includes modified cellulose nanocrystals modified with graphene oxide, and the preparation method of the modified cellulose nanocrystals modified with graphene oxide specifically includes the following steps: dissolving graphene oxide and modified cellulose nanocrystals in N,N-dimethylformamide at a mass ratio of 2:1, ultrasonically dispersing and stirring at a temperature of 60° C. for 35 minutes, filtering, and vacuum drying at a temperature of 80° C. for 26 hours to obtain modified cellulose nanocrystals modified with graphene oxide, i.e., nanofiller B;

[0090] The amount of N,N-dimethylformamide added is just enough to dissolve the graphene oxide and the modified cellulose nanocrystals;

[0091] The modification method of the modified cellulose nanocrystal is:

[0092] The cellulose nanocrystals and DMSO-toluene solution were magnetically stirred evenly, and after the stirring was completed, the modifier was added and mixed evenly and the temperature was controlled at 90°C and stirred for 23 hours, and then cooled to room temperature, and washed with acetonitrile, ethanol and deionized water three times in sequence and centrifuged to obtain modified cellulose nanocrystals;

[0093] The cellulose nanocrystals used in this example were purchased from Guilin Sailun Technology Co., Ltd., with an average length of 40 nm and an average width of 10 nm, model CNC-C;

[0094] The usage ratio of the cellulose nanocrystals, DMSO-toluene solution and the modifier is 1.1 g:320 mL:1.2 g;

[0095] The volume ratio of DMSO to toluene in the DMSO-toluene solution is 8:2;

[0096] The modifying agent includes tert-butyl 3-hydroxy-3-(2-hydroxyethyl)azetidine-1-carboxylate.

[0097] After testing, the modified cellulose nanocrystal modified graphene oxide prepared in this embodiment has an average stacking number of 3 layers and a specific surface area of ​​29m 2 / g, bulk density is 19g / L.

[0098] Example 4

[0099] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0100]

[0101] The epoxy prepolymer comprises a bisphenol A type epoxy resin prepolymer;

[0102] The curing agent comprises ethylenediamine and stannous chloride in a mass ratio of 1:3;

[0103] The nanofiller A includes the modified nano zirconium dioxide obtained in Example 1;

[0104] The nanofiller B includes the modified cellulose nanocrystal-modified graphene oxide obtained in Example 3;

[0105] The synergist comprises ethylene dioleamide, alkylene glycidyl ether and 1,6-hexanediol diglycidyl ether in a mass ratio of 3:1:2;

[0106] The method for preparing the high-transparency, high-strength and high-toughness epoxy resin composite material specifically comprises the following steps:

[0107] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring at 40° C. with ultrasonic assistance for 12 h to obtain a mixture A;

[0108] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture at 25° C. with ultrasonic assistance for 6 h, sealing the mixture and allowing it to stand for 24 h to obtain a mixture B;

[0109] (3) The mixture B is kept at 120° C. and allowed to stand for 9 hours to obtain a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0110] Example 5

[0111] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0112]

[0113] The epoxy prepolymer comprises a bisphenol A epoxy resin prepolymer and a bismaleimide modified phenolic epoxy resin prepolymer in a mass ratio of 3:1;

[0114] The curing agent comprises o-phthalic acid dithiol and isophorone diamine in a mass ratio of 2:3;

[0115] The nano filler A includes the modified nano alumina obtained in Example 2;

[0116] The nanofiller B includes the modified cellulose nanocrystal-modified graphene oxide obtained in Example 1;

[0117] The synergist comprises ethylene bisstearic acid amide and 1,4-butanediol diglycidyl ether in a mass ratio of 1:1;

[0118] The method for preparing the high-transparency, high-strength and high-toughness epoxy resin composite material specifically comprises the following steps:

[0119] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring at 70° C. with ultrasonic assistance for 3 h to obtain a mixture A;

[0120] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring at 35° C. with ultrasonic assistance for 1 h, sealing and standing for 72 h, to obtain a mixture B;

[0121] (3) The mixture B is kept at 155° C. and allowed to stand for 5 hours to obtain a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0122] Example 6

[0123] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0124]

[0125] The epoxy prepolymer comprises a bisphenol A epoxy resin prepolymer and an epoxy silane prepolymer in a mass ratio of 4:3;

[0126] The curing agent comprises o-phthalic acid dithiol, boron trifluoride methanol complex and 1,1-thiocarbonyl diimidazole in a mass ratio of 2:1:3;

[0127] The nanofiller A includes the modified nano-silicon dioxide obtained in Example 3;

[0128] The nanofiller B includes modified cellulose nanocrystal-modified graphene oxide obtained in Example 2;

[0129] The synergist comprises neopentyl glycol diglycidyl ether and benzyl glycidyl ether in a mass ratio of 2:1;

[0130] The method for preparing the high-transparency, high-strength and high-toughness epoxy resin composite material specifically comprises the following steps:

[0131] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring at 60° C. with ultrasonic assistance for 5 h to obtain a mixture A;

[0132] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture at 40° C. with ultrasonic assistance for 4 h, sealing the mixture and allowing it to stand for 42 h to obtain a mixture B;

[0133] (3) The mixture B is kept at 145° C. and allowed to stand for 6 hours to obtain a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0134] Example 7

[0135] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0136]

[0137] The epoxy prepolymer comprises a bisphenol A epoxy resin prepolymer and an epoxy silicone prepolymer in a mass ratio of 3:1;

[0138] The curing agent comprises boron trifluoride methanol complex, m-phenylenediamine and sebacic acid dihydrazide in a mass ratio of 1:2:1;

[0139] The nanofiller A includes the modified nano zirconium dioxide obtained in Example 2;

[0140] The nanofiller B includes modified cellulose nanocrystal-modified graphene oxide obtained in Example 2;

[0141] The synergist comprises ethylene dioleamide, neopentyl glycol diglycidyl ether and phenyl glycidyl ether in a mass ratio of 4:1:1;

[0142] The method for preparing the high-transparency, high-strength and high-toughness epoxy resin composite material specifically comprises the following steps:

[0143] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring at 55° C. with ultrasonic assistance for 8 h to obtain a mixture A;

[0144] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture at 55° C. for 4 h with ultrasonic assistance, and sealing the mixture and allowing it to stand for 72 h to obtain a mixture B;

[0145] (3) The mixture B is kept at a temperature of 137.5° C. and allowed to stand for 8 h to obtain a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0146] Example 8

[0147] A high-transparency, high-strength and high-toughness epoxy resin composite material, the epoxy resin composite material comprising the following raw material components by weight:

[0148]

[0149] The epoxy prepolymer comprises a bisphenol A epoxy resin prepolymer and a bismaleimide modified phenolic epoxy resin prepolymer in a mass ratio of 2:1;

[0150] The curing agent comprises 1,1-thiocarbonyldiimidazole, triethylamine and dicyclic amidine in a mass ratio of 1:1:3;

[0151] The nano filler A includes the modified nano alumina obtained in Example 1;

[0152] The nanofiller B includes the modified cellulose nanocrystal-modified graphene oxide obtained in Example 3;

[0153] The synergist comprises ethylene dioleamide and phenyl glycidyl ether in a mass ratio of 3:2;

[0154] The method for preparing the high-transparency, high-strength and high-toughness epoxy resin composite material specifically comprises the following steps:

[0155] (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring with ultrasound at 47.5° C. for 7.5 h to obtain a mixture A;

[0156] (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture at 60° C. with ultrasonic assistance for 3.5 h, sealing the mixture and allowing it to stand for 48 h to obtain a mixture B;

[0157] (3) The mixture B is kept at a temperature of 137.5° C. and allowed to stand for 3 hours to obtain a finished epoxy resin composite material with high transparency, high strength and high toughness.

[0158] Comparative Example 1

[0159] Compared with Example 6, the difference is that in Comparative Example 1, no nanofiller A is added, while the nanofiller B is 2.3 parts by weight, the synergist is 24.2 parts by weight, and the other operating steps and parameters remain unchanged.

[0160] Comparative Example 2

[0161] Compared with Example 6, the difference is that in Comparative Example 2, no nanofiller B is added, while the nanofiller A is 3 parts by weight, the synergist is 23.5 parts by weight, and the other operating steps and parameters remain unchanged.

[0162] Comparative Example 3

[0163] Compared with Example 6, the difference is that in Comparative Example 3, no synergist is added, but the nanofiller A is 14 parts by weight, the nanofiller B is 12.5 parts by weight, and the other operating steps and parameters remain unchanged.

[0164] Test Case

[0165] (1) Transparency test: According to GB / T 2410-2008, the epoxy resin composite materials prepared in Examples 4-8 and Comparative Examples 1-3 were tested for transparency. Transparency ≥ 80% was considered high transparency. The results are shown in Table 1.

[0166] (2) Toughness test: According to ASTM D256-10, the epoxy resin composite materials prepared in Examples 4-8 and Comparative Examples 1-3 were tested for toughness. I ZOD impact strength ≥ 20 J / m was considered high toughness. The results are shown in Table 1.

[0167] (3) Tensile strength test: According to GB / T 1040-2006, the epoxy resin composite materials prepared in Examples 4-8 and Comparative Examples 1-3 were subjected to a tensile strength test. A tensile strength of ≥40 MPa was considered high strength. The results are shown in Table 1.

[0168] Table 1

[0169] transparency(%) IZOD impact strength (J / m) Tensile strength(MPa) Example 4 81 26 47 Example 5 81 22 40 Example 6 87 28 48 Example 7 85 21 43 Example 8 83 23 41 Comparative Example 1 77 10 29 Comparative Example 2 75 14 27 Comparative Example 3 70 19 35

[0170] It can be seen from the transparency data in Table 1 that the present invention selects different raw materials to be compounded as the curing agent, and the epoxy resin composite materials formed by the reaction of the curing agent under the formula of the present invention and the epoxy prepolymer all have the characteristic of high transparency; in addition, the nanofiller A, nanofiller B and synergistic additive selected in the present invention can exert a synergistic effect, so that the finished epoxy resin composite material has the characteristic of high transparency.

[0171] It can be seen from the data of ZOD impact strength and tensile strength in Table 1I that the epoxy resin composite material prepared in the present invention has the characteristics of high strength and high toughness.

[0172] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0173] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-transparency, high-strength and high-toughness epoxy resin composite material, characterized in that: The epoxy resin composite material comprises the following raw material components in parts by weight:

2. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 1, characterized in that: The epoxy prepolymer includes at least one of bisphenol A epoxy resin prepolymer, bismaleimide modified phenolic epoxy resin prepolymer, epoxy silane prepolymer and epoxy silicone prepolymer.

3. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 1, characterized in that: The curing agent includes at least one of o-phenylenedithiol, ethylenediamine, methylhexahydrophthalic anhydride, boron trifluoride methanol complex, 1,1-thiocarbonyldiimidazole, triethylamine, bicyclic amidine, isophoronediamine, metaphenylenediamine, sebacic acid dihydrazide and stannous chloride.

4. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 1, characterized in that: The nano filler A includes any one of modified nano zirconium dioxide, modified nano alumina and modified nano silicon dioxide; the modified raw material of the modified nano zirconium dioxide is nano zirconium dioxide, the modified raw material of the modified nano alumina is nano alumina, and the modified raw material of the modified nano silicon dioxide is nano silicon dioxide.

5. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 4, characterized in that: The preparation methods of the nanofiller A are: Deionized water and anhydrous ethanol are mixed evenly, and the pH is adjusted to obtain a mixed solution A. A modifier is added to the mixed solution A, mixed evenly, and stirred at a controlled temperature once. After stirring, a modified raw material is added, mixed evenly, and stirred at a controlled temperature twice to obtain a slurry. The slurry is dried at a controlled temperature, extracted with anhydrous ethanol, and an extracted powder is obtained. The extracted powder is dried at a controlled temperature to obtain a nanofiller A. The dosage ratio of the mixed solution A, the modifier and the modified raw material is 200-210 mL: 1-1.2 g: 9-10 g.

6. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 1, characterized in that: The nanofiller B includes modified cellulose nanocrystals modified with graphene oxide.

7. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 6, characterized in that: The preparation method of the modified cellulose nanocrystal-modified graphene oxide specifically comprises the following steps: dissolving graphene oxide and modified cellulose nanocrystals in N,N-dimethylformamide, ultrasonically dispersing and stirring, filtering, and vacuum drying to obtain modified cellulose nanocrystal-modified graphene oxide; The mass ratio of the graphene oxide to the modified cellulose nanocrystals is 2:

1.

8. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 7, characterized in that: The modification method of the modified cellulose nanocrystal is: The cellulose nanocrystals and DMSO-toluene solution are magnetically stirred to be uniform, and after the stirring is completed, a modifier is added to mix uniformly and stirred under controlled temperature, cooled, washed and centrifuged to obtain modified cellulose nanocrystals; The usage ratio of the cellulose nanocrystals, the DMSO-toluene solution and the modifier is 1-1.2 g:300-320 mL:1-1.2 g; The modifier includes any one of 1-N-Boc-3-hydroxyazetidine, 1-benzyl-3-azetidine and 3-hydroxy-3-(2-hydroxyethyl)azetidine-1-carboxylic acid tert-butyl ester.

9. The high-transparency, high-strength, high-toughness epoxy resin composite material according to claim 1, characterized in that: The synergist comprises at least one of ethylene dioleamide, ethylene bis stearic acid amide, alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, benzyl glycidyl ether, neopentyl glycol diglycidyl ether and phenyl glycidyl ether.

10. A method for preparing a high-transparency, high-strength and high-toughness epoxy resin composite material according to any one of claims 1 to 9, characterized in that: The specific steps include: (1) mixing nanofiller A, nanofiller B and a synergist uniformly and stirring with ultrasonic assistance under temperature control to obtain a mixture A; (2) mixing the epoxy prepolymer, the curing agent and the mixture A obtained in step (1) uniformly, stirring the mixture with the aid of ultrasound under temperature control, sealing the mixture and allowing it to stand, to obtain a mixture B; (3) The mixture B is placed under temperature control and allowed to stand, thereby obtaining a finished epoxy resin composite material with high transparency, high strength and high toughness.